TEACHING ENGLISH GRAMMAR AT UNIVERSITY: A Pedagogical and Psychological Reflection Based on an Experimental Research at FKIP Universitas Bung Hatta - Refnita, Lely (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2007)
Grammar is one of important aspects of a language that makes the language learnable and teachable. The teaching of grammar, especially foreign language grammar, needs a serious attention from the teachers and related institutions. Specifically in universities, the teaching of English grammar should provide the students with theoretical concepts of the English grammar and opportunity to use the concepts in their communication. The grammar teaching should also offers suitable assignments by which they may test their language hypothesis. To establish and develop the students’ knowledge about the English grammar, the use of students’ mother tongue as an instructional language in the classroom was considered effective. However, an experimental research conducted by Refnita (2006) showed that the use of Bahasa Indonesia as an instructional language of Grammar I subject was not more effective than the use of English. It is true that bahasa Indonesia is not the students’ mother tongues, but they have mastered it as almost perfectly as their mother tongues. That’s why in her research bahasa Indonesia was considered similar with the students’ mother tongues.The rejection of the proposed research hypothesis implied that pedagogical and psychological factors should be taken into account in the teaching-learning process because the success of learning English grammar does not solely depend upon the instructional language. Further analysis of the research result reflected that the students’ motivation and learning readiness even more determined the success of learning Grammar I. In relation with this phenomenon, the present article, which is based on and developed from the research result, will discuss further the pedagogical and psychological reflections of grammar teaching that need to be considered in the teaching-learning process of English grammar at universities in addition to the use of instructional language.